Idade e crescimento da tartaruga verde, Chelonia mydas, no litoral do Espírito Santo, Brasil - Barreto, Jonathas da Silva (2017)
Green turtle (Chelonia mydas) is a migratory species which dwells in a very different and outlying habitats and locations during its life cycle (from Tropics to Temperate Zones). Despite its life history being geographically largely distributed, it does not receive many attention in a global scale and most of studies aiming to determinate age and growth rate check up on juvenile individuals. This paper brings information about the age in which green turtles recruit to neritic environment, and also introduce the first reports on the maturation age in the western South Atlantic Ocean. Trough skeletocronology, it was shown that the ‘lost years’ duration to the green turtles is at least 2 years, and the average age of maturation is 27 years to western South Atlantic Ocean population. The Body Proportionality Hypothesis was applied to calculate the growth rates. The values found to the South Atlantic population was close to that found at North Atlantic, but bigger than the ones from Pacific Ocean. It suggests that local conditions, as well as genetical determination, may interfere on marine turtles growth rates.